Agribusiness System Of Pomelo Citrus In Pangkajene And Kepulauan Regency - Nur Fa'izah Zainal; Khursatul Munibah; Iskandar Lubis (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Pomelo citrus is a leading commodity in Pangkajene and Kepulauan Regency (Pangkep), yet its production has declined in recent years. The decline in pomelo production and productivity is suspected to be due to an inadequate agribusiness system. This study aims to analyze the agribusiness system in order to enhance the effectiveness of pomelo orchard management. Respondents were selected using purposive sampling, comprising 47 farmers spread across several farmer groups. Interviews were conducted with farmers and buyers, while questionnaires were administered to farmers, collect, and pomelo traders. The analysis included farm business analysis to determine the R/C ratio, marketing margin analysis, and farmer’s share analysis using Microsoft Excel. The results showed that Ma’rang District possesses the most comprehensive subsystems compared to other districts, consisting of input subsystem, production/farming subsystem, agricultural product processing subsystem, marketing subsystem, and support subsystem. The R/C ratio analysis indicates that farming in Ma’rang (1.39), Labakkang (2.47), and Segeri (1.86) remains economically feasible. Five marketing chains were identified, with Marketing Chain 5 (farmer–consumer) being the most efficient, and Marketing Chain 4 (farmer–middleman–trader–consumer) the least profitable. The agribusiness system serves as a guide to enhance the efficiency and effectiveness of government efforts in developing and sustaining pomelo productivity as a flagship commodity in Pangkep Regency.